Psychological adjustment and social capital: a qualitative investigation of Chinese expatriates. Issue 1 (12th February 2019) - He, Beiting; An, Ran; Berry, John
Abstract : Purpose: The purpose of this paper is to explore the psychological adjustment process of expatriates from Chinese multinational enterprises, including how their social capital affects this process. Design/methodology/approach: This qualitative investigation was based on semi-structured, in-depth interviews with 26 Chinese expatriates. The grounded theory method was applied to guide the data collection and analysis. Findings: The psychological adjustment process of Chinese expatriates includes three periods: crisis, self-adjustment and self-growth period. In addition, bonding capital (including organizational, family and co-cultural colleagues' support) is more conducive to Chinese expatriates' psychological well-being than bridging capital (e.g. host-nationals' support). Finally, a separation acculturation strategy is more conducive to psychological adjustment, rather than an integration strategy. Research limitations/implications: This study focused on expatriates themselves. Future research should consider other stakeholders (e.g. organizations, family), and examine expatriate adjustment from new perspectives (e.g. strategic human resource management, work-family balance). This study had a small sample and focused on only one organization. Future research could usefully add other Chinese multinational corporations, and other Chinese expatriates to expand the generalizability of the current findings. Practical implications: This study suggests the possible benefits of management practices for expatriates. Organizations can develop an "expatriate bubble" to help structure basic life overseas. Organizations could develop family-support programs and make them expatriate-supportive. Organizations should also strengthen the connections between expatriates and local colleagues. Originality/value: Few scholars have elaborated on how different support groups (based on their cultural backgrounds) influence the psychological adjustment of expatriates. Until now, mainland Chinese expatriates have received little attention. In addition, this research takes a significant step forward by illuminating the psychological adjustment of Chinese expatriates from a social capital perspective.